2018
DOI: 10.1038/s41598-018-35148-2
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of diabetic nephropathy in db/db mice treated with tibetan medicine formula Siwei Jianghuang Decoction Powder extract

Abstract: Siwei Jianghuang Decoction Powder (SWJH) documented originally in the Four Medical Tantras-Blue Glaze exhibited beneficial effects on diabetic nephropathy (DN) via combined synergistically action of multiple formula components including Curcumae longae Rhizoma, Berberidis dictyophyllae Cortex, Phyllanthi Fructus and Tribuli Fructus. This study investigated the effects of SWJH on DN in db/db mice and possible underlying mechanisms. The ten weeks old db/db mice treated with SWJH by intra-gastric administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The research suggested that VEGFA could serve as biomarkers to identify the progression of DN and had higher expression in the plasma and urine of DN patients [34]. In addition, after treatment with medicine, not only FBG and Scr levels were decreased but also VEGF, HIF-1α, and TGF-β1 mRNA expression was downregulated in DN mice [35]. Meanwhile, NOS3, HIF-1α, and VEGFA play a crucial role in angiogenesis and endothelial cell proliferation.…”
Section: Journal Of Diabetes Researchmentioning
confidence: 99%
“…The research suggested that VEGFA could serve as biomarkers to identify the progression of DN and had higher expression in the plasma and urine of DN patients [34]. In addition, after treatment with medicine, not only FBG and Scr levels were decreased but also VEGF, HIF-1α, and TGF-β1 mRNA expression was downregulated in DN mice [35]. Meanwhile, NOS3, HIF-1α, and VEGFA play a crucial role in angiogenesis and endothelial cell proliferation.…”
Section: Journal Of Diabetes Researchmentioning
confidence: 99%
“…On the other hand, the use of herbal medicines to promote glycemic and metabolic homeostasis in pathological conditions such as DM is becoming increasingly popular in the world’s population [ 24 ]. In this context, supplementation with turmeric ( Curcuma longa L.), in different ways, appears to act beneficially on glycemic control; these effects are partly due to an attenuation of insulin resistance and frequently encountered comorbidities in patients with diabetes [ 25 , 26 ]. Some authors suggest that these effects of turmeric are partly due to the high concentrations of curcumin that have antioxidant action [ 27 – 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these treatments have the same fatal disadvantage when taken the side effects into count. In recent years, traditional Chinese medicine (TCM), a medical system of diagnosis and health care approaches, has achieved extraordinary results in the treatment of DN (Guang‐Dong, Chao‐Yuan, & Wen‐Peng, ; Lai et al, ) and could provide alternative choice for diabetes and its complications.…”
Section: Introductionmentioning
confidence: 99%